Study of biocompatibility strains of bacteria of Lactobacillus, promising as probiotics (Experimental biology, 2015)
This article presents the results of a study of biocompatibility Lactobacillus, namely revealed the nature of their relationship interbacterial on the basis of their co-culture on solid medium. Isolated strains are perspective on thejoint cultivation. Most cultures of lactobacilli exhibit compatibility. The most active strains of L. pentosus 7 LB, L.rhamnosus 10 LB, L. pentosus 12 LB, L. brevis 3 LB, L. casei 11 Г B-RKM.
Keywords: strain; Lactobacillus; аntibacterial activity; interbacterial relationship